Politische Karriere und sozialer Aufstieg. Konservative und christlichsoziale Politiker aus Vorarlberg als Beispiel (1860-1918/19) - SCHNEIDER, Karin (Studia Universitatis Babeș-Bolyai Historia, 2021)
Political Career and Social Advancement. Conservative and Christian Social Politicians from Vorarlberg as an Example (1860-1918/19). As far as the political developments in Vorarlberg were concerned, Martin Thurnher and Johann Kohler have lived in a time of rapid changes. Many of the newly elected deputies to the provincial parliament in 1870, and later also to the Imperial Council, now came from a petty or lower middle-class milieu. For them, political involvement, supported by structural factors such as the successive extension of voting rights to lower social strata, and the increasingly professional self-organization of the Catholic-conservative camp, provided an opportunity for social mobility. Martin Thurnher and Johann Kohler are just two examples of how political engagement enabled social advancement. Further quantitative and qualitative research would provide important insights into the social processes set in motion by the emergence of modern mass parties and the expansion of political participation. Article history: Received 1.12.2021; Revised 27.12.2021; Accepted 30.12.2021; Available online 13.04.2022. Rezumat: Cariera politică şi promovarea socială. Exemplul unor politicieni conservatori şi creştin-sociali din Vorarlberg (1860-1918/19). În ceea ce priveşte evoluţiile politice din Vorarlberg, Martin Thurnher şi Johann Kohler au trăit într-o perioadă de schimbări. Mulţi dintre deputaţii nou aleşi în parlamentul provinciei în 1870, iar mai târziu şi în Consiliul Imperial, proveneau acum din clase sociale inferioare sau cel mult din straturile de jos ale clasei de mijloc. Pentru aceştia, implicarea politică, susţinută de factori structurali precum extinderea succesivă a dreptului de vot şi auto-organizarea tot mai profesionistă a taberei catolice-conservatoare, a reprezentat o oportunitate de mobilitate socială. Martin Thurnher şi Johann Kohler sunt doar două exemple ale modului în care implicarea politică a permis avansarea socială. Alte cercetări cantitative şi calitative vor informaţii importante despre procesele sociale puse în mişcare de apariţia partidelor moderne de masă şi de extinderea participării politice. Cuvinte-cheie: mobilitate socială, parlamentarism, Monarhia Habsburgică, Consiliul Imperial